BIODIESEL ANALYSIS PREPARED FROM WASTE DOMESTIC OIL, THROUGH RMN - Cedrón, Juan Carlos (2014)
Biodiesel was prepared from domestic oil wastes, using the transesterification reaction with ethanol. Yield was 78% and the product was characterized by its physicochemical properties. A detailed analysis of the 1H-NMR spectrum indicated that conversion of triglycerides into mono-alkyl esters was 98.82%, revealing the recommended quality for the biodiesel. Transesterification can be used as an important method to produce biodiesel from domestic oil wastes.